2020
DOI: 10.1186/s42155-020-00116-3
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-oriented puncture for creating an access for endovascular aortic aneurysm repair in a case of iliac and femoral artery occlusion

Abstract: Background: Abdominal aortic aneurysms (AAA) with iliac artery occlusive diseases are not uncommon. When an occlusion extends from iliac artery to common femoral artery (CFA), adjunctive procedures such as endareterectomy of CFA and angioplasty of iliac artery are performed prior to endovascular aneurysm repair (EVAR). Alternatively, aorto-uni-iliac stentgrafting with femoro-femoro bypass surgery could be performed. If run off vessels such as superficial femoral artery (SFA) and profunda femoris artery (PFA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…Endovascular treatment presents fewer periprocedural complications but has less durability compared to bypass surgery, which is associated with short-term increase in morbidity and has longer durability, thus decreasing the reintervention rate. 5 The BASIL trial compared these two treatment options, and the results at two years of followup did not show differences between the two techniques.…”
Section: Discussionmentioning
confidence: 97%
“…Endovascular treatment presents fewer periprocedural complications but has less durability compared to bypass surgery, which is associated with short-term increase in morbidity and has longer durability, thus decreasing the reintervention rate. 5 The BASIL trial compared these two treatment options, and the results at two years of followup did not show differences between the two techniques.…”
Section: Discussionmentioning
confidence: 97%
“…To introduce the endograft via an occluded access involving the CFA, the authors previously reported a technique where an angioplasty balloon was advanced distally to the occluded CFA via the occluded iliac artery from the contralateral CFA (Ichihashi et al 2020 ). The balloon was then punctured under fluoroscopy consequently establishing a through and through wire between the bilateral CFAs.…”
Section: Discussionmentioning
confidence: 99%
“…En los últimos años los dispositivos y las técnicas intervencionistas han evolucionado considerablemente y algunos estudios han observado que el tratamiento endovascular de lesiones oclusivas aortoilíacas extensas no es inferior al de la cirugía abierta (3)(4)(5). Se han realizado varias series que evalúan la eficacia del tratamiento endovascular e híbrido de TASC II C y D en la patología aortoilíaca (2,4), pero solo unas pocas han comparado directamente ambas técnicas (3,4).…”
Section: Discussionunclassified
“…Como acceso vascular, aunque el acceso femoral sigue siendo de elección para el tratamiento de lesiones ilíacas, pueden utilizarse sitios alternativos, como la arteria pedia, la AFS y las radiales para dar apoyo en una lesión altamente calcificada en caso de que la arteria femoral común esté enferma o para reducir las complicaciones del acceso vascular asociadas con la punción de la arteria femoral (5,6).…”
Section: Discussionunclassified